How to deal with conflict without using violence? Analysis of the colombian state and the law of victims, taking away arguments to illegal armed groups (2019)
The Colombian conflict has been one of the longest running disputes in the Western world. Although the signing of the peace treaty in 2016 gave hope back to the territory, this process did not happen overnight, so it was necessary to go through a historical journey to get the results today, where one of its fundamental milestones was the law of victims and the framework for peace. Through a review of the literature, this article seeks to analyze the impact on the Colombian conflict and the dynamics of the actors involved from the perspective of the law of victims. Among the most significant findings is that the Victims’ Law should not be seen as a panacea to solve all the country’s problems. Few recognize that it is a first step in the right direction, and the government’s courage to take it must be stressed. In that sense, the authorities must show good intentions, imagination and political will to allow the military response on the one hand, and generate and implement initiatives and policies with facts on the other hand.